Basic assumptions of nursing care for a patient after rotational atherectomy - Tkaczyk, Filip M. (Nursing Problems / Problemy Pielęgniarstwa, 2023)
The increase in the average age of patients contributes to the occurrence of more cases of severe calcification of the coronary arteries. Advanced pathologies are less susceptible to classical therapeutic methods, such as coronary angioplasty. An alternative technique is rotational atherectomy, which invasively removes the atherosclerotic plaque, preparing the vessel for further therapeutic interventions. The progress in the popularity of this method requires the use of knowledge at the highest level by the medical staff taking care of the patient. The risk of severe complications generates several nursing problems. Nursing staff observation, monitoring of basic vital signs, and pharmacotherapy contribute to the proper course of hospitalization. By implementing elements of health education, it strengthens the patient’s attitude to the therapeutic process and the introduction of beneficial lifestyle modifications. The aim of the paper is to present the basic assumptions of nursing care for patients after rotational atherectomy.